Stable carbon isotope fractionation by methanogens growing on different Mars regolith analogs. (July 2015) - Sinha, Navita; Kral, Timothy A.
Abstract: In order to characterize stable carbon ( 13 C/ 12 C) isotope fractionation of metabolically produced methane by methanogens in martian settings, Methanothermobacter wolfeii, Methanosarcina barkeri, and Methanobacterium formicicum were cultured on four different Mars regolith analogs – JSC Mars-1, Artificial Mars Simulant, montmorillonite, and Mojave Mars Simulant – and also in their growth supporting media. These chemoautotrophic methanogens utilize CO2 for their carbon source and H2 for their energy source. When compared to the carbon isotope signature of methane when grown on their respective growth media, M. wolfeii and M. barkeri demonstrated variability in carbon isotope fractionation values during methanogenesis on the Mars analogs, while M. formicicum showed subtle or negligible difference in carbon isotope fractionation values. Interestingly, M. wolfeii and M. barkeri have shown relatively consistent enriched values of 12 C on montmorillonite, a kind of clay found on Mars, compared to other Mars regolith analogs. In general, M. barkeri showed large carbon isotope fractionation compared to M. wolfeii and M. formicicum during methanognesis on various kinds of analogs. Stable carbon isotope fractionation is one of the techniques used to infer different origins, environments, and pathways of methanogensis. The results obtained in this novel research can provide clues to determine ambiguous sources of methane on Mars. Highlights: Methangens produced less methane on Mars regolith analogs compared to growth media. Methanogens demonstrated large stable carbon isotope fractionation on Mars analogs . Methanosarcina barkeri demonstrated the largest stable carbon isotope fractionation.